Probing surface interactions in CdSe quantum dots with thiocyanate ligands - Deshmukh, Samadhan H.; Yadav, Sushma; Chowdhury, Tubai; Pathania, Akhil; Sapra, Sameer; Bagchi, Sayan (NANOSCALE, 2024)
Keywords: COLLOIDAL NANOCRYSTALS; STRUCTURAL DYNAMICS; Thin-films

Slowdown of solvent structural dynamics in aqueous DMF solutions - Pathania, Akhil; Bagchi, Sayan (Chemical Physics Impact, 2024)
<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">This study presents a comprehensive investigation into the molecular dynamics of solvation environments through an integrated approach combining Fourier-transform infrared (FTIR) spectroscopy, molecular dynamics (MD) simulations, and two-dimensional infrared (2D IR) spectroscopy. We explore the solvation of an ionic solute (ammonium thiocyanate) in various solvent systems, including N,N-dimethylformamide (DMF), water, and a 0.5 mole fraction of DMF in water, aiming to unravel the intricate interplay between solute-solvent interactions and solvent dynamics across diverse solvation environments. By integrating FTIR spectral analysis with radial distribution functions and coordination numbers obtained from MD simulations, we decipher the solvent composition around the solute molecule. Analysis of 2D IR spectra and hydrogen bond, as well as dipolar autocorrelation function from MD simulations, further elucidates the nuances of solute-solvent interactions, highlighting the impact of solvent dynamics on solvation structures. Our results reveal a significant slowdown of the solvent structural dynamics in the equimolar binary solvent mixture compared to the neat solvents. This slowdown underscores the complex relationship between solute-solvent interactions and solvent dynamics. The integration of FTIR, MD simulations, and 2D IR spectroscopy provides a unified framework for obtaining a holistic understanding of solvation dynamics, offering valuable insights into the underlying molecular mechanisms governing solute-solvent interactions in complex systems. These results pave the way for future studies to delve deeper into the molecular intricacies of solvation phenomena.

Probing solvent fluctuations in deep eutectic solvents: Influence of probe charge and nano-domain localization - Chowdhury, Tubai; Pathania, Akhil; Ravindranathan, Sapna; Bagchi, Sayan (Journal of Chemical Physics, 2025)
Deep eutectic solvents (DESs) segregate into hydrogen bond acceptor or hydrogen bond donor (HBD) rich nano-domains, leading to molecular heterogeneity. Understanding how this heterogeneity affects the DES structure and dynamics is essential. In this study, we used two-dimensional nuclear magnetic resonance (2D NMR) and two dimensional infrared (2D IR) spectroscopies, combined with molecular dynamics (MD) simulations, to investigate solvation structure and dynamics in two choline chloride-based DESs with different HBDs-levulinic acid and glycolic acid. We introduced two thiocyanate vibrational probes, methyl thiocyanate (CH3SCN, neutral) and ammonium thiocyanate (NH4SCN, anionic), which selectively localize in specific nano-domains. 2D NMR provided insights into solvent structure and probe location, while 2D IR captured solvation dynamics. Our results show that these small probes do not alter the solvent structure, regardless of charge. However, solvation dynamics depend on long-range electrostatic ordering in the DES and the local shielding effects of the nano-domain where the probe resides. MD simulations complement experimental findings, providing a molecular-level understanding of solvation in DESs.